Base metals- and Lithium- rich ferromanganese oxide deposits from the South Andaman Sea, Northeastern Indian Ocean: Mode of occurrence and genesis. (15th August 2022) - Rajani, Plamchuvatil Ramesh; Manoj, R.V.; Joshi, R.K.; Jishnu, B.K.; Nagasundaram, M.
Graphical abstract: Highlights: South Andaman Sea hosts ferromanganese oxide deposits in areas shallower than 2000 m water depth. Ni, Zn, Pb, Li, As and Ba enrichments in crusts and nodules imply predominance of hydrothermal source. Metal saturated semi-enclosed basin ventilated by intermediate waters expedited accretion of Fe-Mn oxides in shallower depths. Hydrothermal metal supply and proximity to intermediate waters govern the regional heterogeneity in genesis of Fe-Mn oxides. Abstract: The Andaman Sea hosts ferromanganese (Fe-Mn) oxide deposits as crusts and nodules over seamounts and ridges shallower than 2000 m water depths. Fe-Mn crust and nodules were recovered from West Sewell Ridge (WSR), Sewell Rise (SR) and Invisible Bank (IB) in the South Andaman Sea. The samples from WSR and SR are enriched in Ni (1628 – 7681 ppm), Pb (500 – 2935 ppm), Zn (372 – 7351 ppm), Li (3 – 781 ppm), Ba (710 – 8672 ppm) and As (119 – 414 ppm) and depleted in Co and Cu. Base metals (Ni + Pb + Zn) are enriched to a maximum concentration of 1.6 % (with an average of 0.7 %) in the WSR and a maximum of 0.7 % (with an average of 0.5 %) in the SR. Nodules from both WSR and SR have consistently higher content of Li, Ba and base metals than Fe-Mn crusts. Fe-Mn nodules and crusts from WSR and crusts from SR are formed predominantly by hydrogenetic precipitation. Fe-Mn nodules from SR have mixed hydrogenetic-hydrothermal origin. Samples from IB are Fe-rich ironstones enriched in Cr, Ni and As that precipitated from hydrothermal solutions percolated through ultramafic rocks. Saturation of deeper waters with metal ions emanating from volcanic-hydrothermal sources and oxygen supply to the basin by intermediate waters together facilitated rapid precipitation of Fe-Mn oxyhydroxides over seamounts and ridges shallower than 2000 m water depths in the Andaman Sea. The rapid precipitation of Fe-Mn oxy-hydroxides in turn constrained the enrichment of elements (especially Co and REEs) that are generally incorporated by slow-hydrogenetic precipitation.